Openlearning platform for UniSZA medical students in anaesthesia - Mohd Faeiz, Pauzi; Siti Norazlina, Juhari (2018)
From micro-computer, disc, computer assisted learning and then to the evolution of the internet, nowadays the trend are using mobile devices, video streaming, world wide technology, compression technology, wide band data network, powerful processors, social-technical innovation, gamification, artificial intelligent and augmented reality. The aim to use the technology to optimise teaching and learning experience, teachers teach by using technology, learners learn through application of ICT, and application of ICT to enables new choices for teaching and learning.